PEMBERDAYAAN DAN PENDAMPINGAN E-COMMERCE UMKM DESA KRIYAN KECAMATAN KALINYAMATAN KABUPATEN JEPARA - Roosdhani, M. Rifqy; Ali, Ali; Sholahuddin, Muchammad (LPPM Universitas Nusa Mandiri, 2023)
Micro, small and medium enterprises (MSMEs) have an important role in the Indonesian economy. Indonesia's increasing economic growth cannot be separated from the role of MSMEs. In particular, the contribution of MSMEs to Gross Domestic Product (GDP). Of course, e-commerce can also be an access for MSMEs to enter international markets. As technology develops, it becomes easier to do this, so this opens up opportunities for MSMEs to be able to optimize company operations and e-commerce. To make this happen, of course, cooperation from various parties is needed, from the government, e-commerce practitioners, academics, economic actors, and of course community support. It is hoped that e-commerce will be able to encourage the progress of MSMEs in Indonesia and especially in Kriyan Village in order to increase Indonesia's economic growth. The community service method is carried out through socialization, lectures and discussions, mentoring/practice and evaluation so that targets and goals are achieved according to targets. The result of this service activity is that the MSMEs are very enthusiastic about participating in online marketing training. Kriyan Village MSMEs have used social media as a marketing medium with a composition of 90% Instagram, 25% Tiktok and 50% Facebook, or it could be said that 85% of the skills of Kriyan Village MSMEs have increased so that they are able to operate digital marketing in promotional media. MSMEs not only know this, but they can also identify social media models that can be used as marketing material.